Functional Complement Analysis Can Predict Genetic Testing Results and Long-Term Outcome in Patients With Complement Deficiencies - Blazina, Štefan; Debeljak, Maruša; Košnik, Mitja; Simčič, Saša; Stopinšek, Sanja; Markelj, Gašper; Toplak, Nataša; Kopač, Peter; Zakotnik, Breda; Pokorn, Marko; Avčin, Tadej (Frontiers in Immunology, 2018)
Background: Prevalence of complement deficiencies (CD) is markedly higher in Slovenian primary immunodeficiency registry (PID) in comparison to other national and international PID registries. Objective: The purposes of our study were to confirm CD and define complete and partial CD in registered patients in Slovenia, to evaluate frequency of clinical manifestations and to assess the risk for characteristic infections separately for subjects with complete and partial CD. Methods: Complement deficiency was confirmed with genetic analyses in patients with C2 deficiency, C8 deficiency and hereditary angioedema (HAE) or with repeated functional complement studies and measurement of complement components in other CD. Results of genetic studies (homozygous subjects vs. heterozygous carriers) and complement functional studies were analyzed to define complete (complement below the level of heterozygous carriers) and partial CD (complement above the level of homozygous patients). Presence of characteristic infections was assessed separately for complete and partial CD. Results: Genetic analyses confirmed markedly higher prevalence of CD in Slovenian PID registry (26% of all PID) than in other national and international PID registries (0,5 – 6% of all PID). Complement functional studies and complement component concentrations reliably distinguished between homozygous and heterozygous CD carriers. Subjects with partial CD had higher risk for characteristic infections than previously reported. Conclusion: Results of our study imply under-recognition of CD worldwide. Complement functional studies and complement component concentrations reliably predicted risk for characteristic infections in patients with complete or partial CD. Vaccination against encapsulated bacteria should be advocated also for subjects with partial CD and not limited to complete CD.